1988
DOI: 10.1073/pnas.85.20.7670
|View full text |Cite|
|
Sign up to set email alerts
|

Asbestos fibers mediate transformation of monkey cells by exogenous plasmid DNA.

Abstract: We have tested the ability of chrysotile asbestos fibers to introduce plasmid DNA into monkey COS-7 cells and the ability of this DNA to function in both replication and gene expression. Chrysotile fibers are at least as effective as calcium phosphate in standard transfection assays at optimal ratios of asbestos to DNA. After transfection with chrysotile, a minor percentage of introduced plasmid DNA bearing a simian virus 40 origin of replication replicates after 24 hr. Fragmentation of entering DNA is more pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(32 citation statements)
references
References 40 publications
0
32
0
Order By: Relevance
“…There are some data that lend support to this hypothesis: (1) the increase in mesothelioma incidence occurred after millions of people, including adults, were injected with SV40-contaminated vaccines; (2) tissue culture experiments indicated that asbestos facilitated transformation of mouse cells by plasmid DNA and by SV40 (Appel et al, 1988;Dubes, 1993); and (3) mesotheliomeas developed in hamsters injected with SV40 (Cicala et al, 1993).…”
Section: Sv40 and Mesotheliomamentioning
confidence: 99%
“…There are some data that lend support to this hypothesis: (1) the increase in mesothelioma incidence occurred after millions of people, including adults, were injected with SV40-contaminated vaccines; (2) tissue culture experiments indicated that asbestos facilitated transformation of mouse cells by plasmid DNA and by SV40 (Appel et al, 1988;Dubes, 1993); and (3) mesotheliomeas developed in hamsters injected with SV40 (Cicala et al, 1993).…”
Section: Sv40 and Mesotheliomamentioning
confidence: 99%
“…It has been generally accepted that like other asbestos types, chrysotile fibers are capable of inducing human malignant mesothelioma [25][26][27][28] . This conclusion has been obtained from various sources including molecular biological studies [29][30][31][32][33] , animal experiments 2,15,[34][35][36][37][38] , epidemiological studies [39][40][41][42][43][44] , case reports [45][46][47][48] , and asbestos tissue burden studies 6,20) . The present study on asbestos tissue burden further supports the evidence that chrysotile fibers were capable of inducing human malignant mesothelioma, since a) chrysotile was the most common asbestos type seen in the mesothelial tissues which is the original site of the induction of mesothelioma and b) chrysotile was exclusively seen in both the lung and the mesothelial tissues in 15/64 (23.3%) cases, in the lung tissue alone in10/43 (23.3%) and in the mesothelial tissues alone in 30/44 (68.2%) cases.…”
Section: Commentsmentioning
confidence: 99%
“…Immortalized cells are usually not able to induce tumours but may become oncogenic if they are transfected with an oncogene, or if they are treated with a carcinogen such as asbestos. A synergistic effect between asbestos and SV40 was suggested by the fact that asbestos facilitates transformation of cells in culture by SV40 [19]. In tumours developing in SV40 transgenic mice and in human cells in culture, transient expression of t-antigen seems to be sufficient to induce transformation.…”
Section: Discussionmentioning
confidence: 99%